ANALISIS KONTROL DIRI TERHADAP PERILAKU BERUTANG PADA IBU RUMAH TANGGA - Udiarti, Luluk; Hamiyati, Hamiyati; Zulfa, Vania (JKKP (Jurnal Kesejahteraan Keluarga dan Pendidikan), 2022)
Along with the development of time, globalization has made people's consumption patterns more complex and diverse. People who buy goods beyond the limits of need can lead to debt behavior. This study aims to analyze the effect of self-control on the debt behavior of housewives in Cileungsi District, Bogor Regency. This research method uses a quantitative approach with a cross-sectional design. The sampling technique used was purposive sampling with a total sample of 120 housewives who met the criteria. The research location was chosen purposively in Pasir Angin Village, Cileungsi District, because it is an area with a high population density and a strategic location with a shopping center. The data were analyzed using a simple linear regression test. The results showed that more than half of housewives had self-control in managing their finances. Then the results of the study also show that housewives have a low category in debt behavior. This study found a negative influence on self-control on debt behavior in housewives. It means that the higher self-control of housewives can lower their debt behavior of housewives. Through proper self-control, it is hoped that debt behavior can decrease in the community.